The Pecking Order Theory Perspective in the Study of Company Capital Structure (Study On Manufacturing Companies On The Indonesia Stock Exchange) - Ika Oktaviyanti; Sumartik Sumartik (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
A balanced combination of own capital and debt is the main key to optimal capital structure in a corporation. At any given time, the management team in the company will show you a targeted capital structure, which may be optimal, althought that target may change from time to time. Several factors influence the company’s capital structure decisions such as Profitability, Liquidity and Company Size. This study was used to measure the impact of profitability, liquidity and firm size on the capital structure of manufacturing companies on the Indonesian stock exchange for the period 2018-2021 using the pecking order theory method. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange. Sampling method used targeted sampling method and obtained his 40 samples from Indonesian Stock Exchange-listed manufacturing companies in the period 2018-2021. Analysis of the data used is multiple linear regression analysis using the SPSS application. Simultaneously the results obtained from this study are the variables of Profitability, Liquidity and Company Size have a significant effect on Capital Structure.